Analysis of the Survey of Social Value of High-quality Farmers in Hubei Province, China - Huang, Yunxue (International Journal of Social Sciences and Public Administration, 2024)
In order to promote the quality and efficiency of high-quality farmers and to improve the training mechanism, we must give full play to the agricultural radio and television school system. The research adopts the method of comprehensive survey of grassroots rural organizations in Hubei province and of sample survey in some cities to track the realization of social value of high-quality peasant students. The research results show that recent development requirements demand high-quality farmers to realize their social value, which suggests the problems of insufficient policy support and implementation, the imperfect growth mechanism of high-quality farmers, and the shortcomings of their ability. In order to achieve the goal of training high-quality farmers, it is necessary to take seriously the survey data from the frontline, grass-roots rural organizations, focusing on the technical support for rural talents, the further implementation of policies, the increase of financial support, and effective implementation of the quality and efficiency of the training of high-quality farmers.